Cervical ectopic pregnancy. Report of two cases - Atamari-Anahui, Noé (2020)
Background. Cervical ectopic pregnancy is the implantation of the embryo in the lining of ​​the endocervical canal lining. It represents less than 1% of all ectopic pregnancies. Case description: We report two patients who come to the emergency room for transvaginal bleeding. The diagnosis of cervical ectopic pregnancy was made by transvaginal ultrasound (7- and 8-weeks' gestation). Treatment was started with methotrexate (28-year-old patient) and methotrexate-folinic acid (35-year-old patient). Due to the increase in human chorionic gonadotropin hormone, it was decided to perform an abdominal hysterectomy (28-year-old patient) and McDonald-type cervical curettage-cerclage (35-year-old patient). There were no complications after surgery in both patients. Conclusions: The treatment of cervical ectopic pregnancy is controversial. The most appropriate therapy should be chosen to preserve fertility and avoid complications such as bleeding.